GRAMMATICAL CHARACTERISTICS OF FUNCTION WORDS (American Journal of Pedagogical and Educational Research, 2026)
In this article, the grammatical features of the auxiliary, conjunction, and predicate, their differences, similarities, origin, and usage will be discussed.